2017
DOI: 10.1111/ejh.12955
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide induces haematologic responses in patients with β‐thalassaemia

Abstract: In this study, thalidomide showed an outstanding effect on β-thalassaemia patients who required frequent red-cell transfusions. Thalidomide increased haemoglobin levels without causing serious adverse reactions, but the long-term curative outcomes and other side effects should be observed continuously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…The reduction in splenomegaly and hypersplenism would also explain the significant elevation in leukocyte count, apparent improvements in hemoglobin level and absolute neutrophil count (non-significant), and low requirement for red blood cell transfusion that were observed in patients treated with thalidomide. Our findings regarding the possible beneficial effects of thalidomide on hemoglobin level and spleen length are in good agreement with those reported in our previous study of nine patients with b-thalassemia who were treated with thalidomide for 6 months or more (Chen et al, 2017). Two case reports have also described an increase in hemoglobin level in response to thalidomide (Aguilar-Lopez et al, 2008;Masera et al, 2010), consistent with the trends in our observations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The reduction in splenomegaly and hypersplenism would also explain the significant elevation in leukocyte count, apparent improvements in hemoglobin level and absolute neutrophil count (non-significant), and low requirement for red blood cell transfusion that were observed in patients treated with thalidomide. Our findings regarding the possible beneficial effects of thalidomide on hemoglobin level and spleen length are in good agreement with those reported in our previous study of nine patients with b-thalassemia who were treated with thalidomide for 6 months or more (Chen et al, 2017). Two case reports have also described an increase in hemoglobin level in response to thalidomide (Aguilar-Lopez et al, 2008;Masera et al, 2010), consistent with the trends in our observations.…”
Section: Discussionsupporting
confidence: 93%
“…However, adverse reactions to thalidomide are rare in other patients. Indeed, we observed no adverse reactions to thalidomide in our previous study of patients with thalassemia ( Chen et al., 2017 ). Thus, we believe that thalidomide would be well tolerated by non-pregnant patients with hypersplenism and thrombocytopenia secondary to cirrhosis or thalassemia.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…12 Moreover, thalidomide is an HbF inducer that promotes γ-globin gene expression. 13,14 A few case reports and retrospective analyses have documented significant effects of thalidomide on NTDT or TDT, [15][16][17][18][19][20] that our group subsequently confirmed in a clinical trial. 21 However, the reliability of these studies was softened by the few patients studied and short-term follow-up.…”
mentioning
confidence: 55%
“…Together with its derivate pomalidomide, it also exhibits a secondary, less characterised effect in increasing γ-globin expression, suggesting a possible role in the control of IE [97]. Besides isolated reports of safety and efficacy of this approach [98,99], the few studies conducted in the last years on patients affected by TDT and NTDT reported promising results in terms of Hb rise and transfusion independence [100,101]. However, these studies involved a very limited number of patients, and high variability was observed in baseline characteristics of the study populations, including extreme conditions such as baseline Hb ≤ 4.0 g/dL in 4 out of 25 patients.…”
Section: Thalidomidementioning
confidence: 99%